Knowledge of bout duration influences pacing strategies during small-sided games - Sampson, J. A.; Fullagar, H. H. K.; Gabbett, T. (Journal of Sports Sciences, 2015)
This investigation examines pacing during intermittent team sports. Sixteen junior Rugby League players participated in eight different small-sided offside touch games. All games were 24 min, but bout durations differed in continuous (1 × 24 min) or repeated (2 × 12, 3 × 8, 4 × 6, 6 × 4, 8 × 3, 12 × 2 or 24 × 1 min) formats. Repeat bouts were interspersed by 2 min of passive rest, and participants were informed of the bout duration immediately prior to the game. Heart rates, ratings of perceived exertion and data gathered from global positioning system devices were used to investigate the pacing strategies employed within each game. No significant (P > 0.05) between-game differences were observed in total distance; however, during the 1-min bouts, high-speed movement was significantly (P < 0.05) increased, during the first and second quarters of the 24 × 1-min game compared to all other formats (effect size range: 0.75 ± 0.61-1.38 ± 0.47). Furthermore, the rate of decline in high-speed movement over-time was greatest during the 24 × 1-min game with large differences observed between the first and third quarters (effect size: 0.90 ± 0.58). Greater moderate-speed (effect size range: 0.62 ± 0.63-1.56 ± 0.40) and less low-speed (effect size range: 0.69 ± 0.62-1.54 ± 0.40) distances were also observed during the 1-min bouts, yet heart rates were higher during the continuous 1 × 24-min game. Pacing strategies during intermittent activities are influenced by the number and duration of exercise bouts. Practitioners should consider within-game bout durations when prescribing game-based activities to improve aerobic capacity.